Twister on Tuesday - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2001)
When Jack and Annie travel back to the Kansas prairie in search of "something to learn," they gain an understanding of how hard life was for pioneers and they experience the terror of a tornado.
"A Stepping Stone book.".
3.2
3-6
Keywords: Annie (Fictitious character : Osborne) -- Fiction; Frontier and pioneer life -- Kansas -- Fiction; Jack (Fictitious character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tornadoes -- Fiction; Tree houses -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Frontier and pioneer life -- Kansas -- Fiction; Jack (Fictional character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tornadoes -- Fiction; Tree houses -- Fiction; Kansas -- Fiction; Kansas -- Fiction